Wandering into Brave new world - Higdon, David Leon, 1939- (Costerus ;, 2013)
"Wandering into Brave New World explores the historical contexts and contemporary sources of Aldous Huxley's 1932 novel which, seventy years after its initial publication remains the best known and most discussed dystopian work of the twentieth century. This new study addresses a number of questions which still remain open. Did his round-the-world trip in 1925-1926 provide material for the novel? Did India's caste system contribute to the novel's human levels? Is there an overarching pattern to the names of the novel/s characters? Has the role of Hollywood in the novel been underestimated? Is Lenina Crown a representative 1920s "flapper"? Did Huxley have knowledge of and sources for his Indian reservation characters and scenes quite independent of and more accurate than those of D.H. Lawrence's writings? Did Huxley's visit to Borneo contribute anything to the novel? New research allows substantive answers and even explains why Huxley linked such figures as Henry Ford and Sigmund Freud. It also shows how the novel overcomes its intense grounding in 1920s political turmoil to escape into the timelessness of dystopian fiction."--Publisher website